Situational tasks as form of interactive studying of medical parasitology (Experimental biology, 2015)
In article possibility of application of situational tasks of medical parasitology as one of forms of interactive training is considered. Use of situational tasks promotes formation of clinical thinking of students, encourages creative dispute, stimulates students and gives them feeling of satisfaction with a work result, increases interest to studied discipline. Work on the solution of situational tasks on occupations is carried out as individually, and in a group form, probably joint discussion of the most difficult questions.
Keywords: solution of situational tasks; interactive methods of training; medical parasitology